Future Access Enablers for Ubiquitous and Intelligent Infrastructures: 4th EAI International Conference, FABULOUS 2019, Sofia, Bulgaria, March 28-29, 2019, Proceedings - Poulkov, Vladimir (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering (283), 2019)
This book constitutes the refereed post-conference proceedings of the Fourth International Conference on Future Access Enablers for Ubiquitous and Intelligent Infrastructures, FABULOUS 2019, held in Sofia, Bulgaria, in March 2019. This year's conference topic covers Globalization through Advanced Digital Technologies - as the digitalization in all spheres of life has an impressive influence on communication and daily life in general. The 39 revised full papers were carefully reviewed and selected from 54 submissions. The main topics deal with: healthcare/wellness applications; IoT and sensor networks; IoT security in the digital transformation era; wireless communications and networks; virtual engineering and simulations.